Uji Aktivitas Ekstrak Etanol dan Akuades Umbi Rumput Teki (Cyperus rotundus L.) Sebagai Repellent Terhadap Nyamuk Aedes aegypti - Naelaz Zukhruf Wakhidatul Kiromah; Siti Inayah; Satria Eta Mulyana; Zalsa Billa; Syifa Churrohmah; Rizki Nur Azizah (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2024)
The dengue virus is one of the causes of Dengue Fever (DF) and is transmitted through the bite of Aedes aegypti mosquitoes. The tuber of the nutgrass plant contains flavonoid compounds known to have insect-repellent activity. This research aims to determine the repellent activity and % protection value of 96% ethanol and water extracts of nutgrass tubers (Cyperus rotundus L.). The research was conducted using male white rats with a repellent test method, and the data generated is the percentage of protection. The concentrations of 1.5%, 3%, and 6% of nutgrass tuber 96% ethanol extract exhibited repellent activity with percentage protection values of 42.7%, 54.02%, and 73.84%, respectively. The aqueous extract of nutgrass tubers showed percentage protection values of 46.34%, 58.66%, and 72.94%, respectively. These results were statistically significant (p<0.05). The research findings indicate that a concentration of 6% provides the highest protection against mosquito bites for both extracts.